O disfemismo: palavras como armas um enfoque da linguística sistêmico-funcional - Bertelli, Adriana Baldas Kutz (2024)
Politicians and speakers use words as weapons to exercise ideological control and ostensibly make the audience believe in their proposals. In this sense, they make use of persuasive resources, such as dysphemism - an offensive word or phrases - as a rhetorical strategy in political discourse, in which the language user intensifies aspects of unacceptable use of a given concept in order to deliberately threaten the face of the listener (i.e., someone's public image) or the face of a third party involved in the communicative act. In such matter, focus to be considered, although few studies have taken the dynamic perspective of considering the interaction between linguistic choices in the construction of rhetorical strategies in the flow of meaning. This perspective relies on the theoretical-methodological proposal of Systemic-Functional Linguistics (SFL), for which the process of language use is a semiotic process, a process of making meaning through choices, an important issue in critical analyses. The objective of this doctoral dissertation is to examine dysphemism in public discourse , based on in newspaper opinion articles and editorials, published in the newspaper Folha de S.Paulo, targeting former President Jair Bolsonaro, candidate for reelection in 2022. Therefore, this research answers the questions: (a) Might dysphemism have contributed to prevent Bolsonaro’s reelection? (b) What was the Appraisal Theory’s contribution concerning the dysphemism analysis in public speech? SFL involves the concept of appraisal, the evaluative lexicon that expresses the speaker's (or writer's) opinion on the good/bad parameter. This is a development of the interpersonal metafunction of this theory, which integrates the analysis of dysphemism in this study, with the support of rhetorical resources of persuasion. Furthermore, the analysis of political rhetoric resorts to the notion of metaphor and its relation to metonymy within the framework of the conceptual theory – an important feature of persuasive rhetoric. The results were obtained through interpretations made in the following sources published by the Folha de S.Paulo newspaper: 6 editorials and 4 opinion articles, published in 2021 and 2022. The results show the strength of dysphemism in supporting the proposal of editorials and opinion articles to prove Bolsonaro's inability as president of Brazil